KUANTIFIKASI JUMLAH LIMBAH ORGANIK DALAM BENTUK PADATAN TERSUSPENSI (TSS) YANG DIKELUARKAN DARI KEGIATAN TAMBAK UDANG INTENSIF - Abdul Muqsith (Faculty of Science and Technology University Ibrahimy, 2014)
The purpose of this study was to determine the amount of organic waste in the form of suspended solids (TSS) discharged from intensive shrimp ponds activity. Research conducted in the area of ​​the District of intensive shrimp aquaculture Banyuputih Stubondo district for four months using a survey method. To determine the amount of organic waste generated from shrimp farms, shrimp feed data retrieval performed during one cycle maintenance, comprehensive data is a pond, stocking density, pond water volume and turnover volume of pond water every day. Quantification of organic waste refers to formula Soewardi (2002). Based on calculations, the total amount of waste oganik in the form of suspended solids (TSS) issued intensive shrimp ponds into coastal waters in a season maintenance of shrimp is 2,277 kg TSS / 3.500 m2 / MT or if it is converted into an area of ​​1 ha pond is 6,506 kg TSS / ha / MT. If all the land productive pond (39 ha) in the study area did the same production during the growing season / maintenance of shrimp, the coastal waters Banyuputih will receive a load of organic waste (TSS) amounted to 253 734 kg in the first season of planting / maintenance shrimp.